A modified plastic ultra-thin test specimen and its preparation method and application

By grinding the modified plastic particles into powder and performing a hot pressing process under the protection of inert gas, ultra-thin test splines with a thickness of 0.3 to 0.9 mm was prepared, which solved the problem of difficulty in preparing ultra-thin splines, and achieved more accurate material performance evaluation and process simplicity.

CN119752149APending Publication Date: 2025-04-04BEIJING HUATENG JINGYAN TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411467936.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

It is difficult to prepare ultra-thin test splines with a thickness of 0.3 to 0.4 mm, and cannot meet the demand for thinner test splines in the field of thin-walled plastic products.

Method used

The modified plastic particles are ground into powder, and a plastic sheet or film is made by hot pressing process under the protection of inert gas, and cut into test splines to achieve ultra-thin test spline preparation with a thickness of 0.3 to 0.9 mm.

Benefits of technology

The successful preparation of ultra-thin test splines with thickness meet the requirements can more accurately evaluate the material performance, and the material consumption is small, making the process simple and easy to perform.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752149A_ABST
    Figure CN119752149A_ABST
Patent Text Reader

Abstract

The present invention provides a modified plastic ultra-thin test strip and a preparation method and application thereof, wherein the thickness of the test strip is 0.3 to 0.9 mm; the present invention prepares the ultra-thin test strip by grinding modified plastic particles into powder and hot pressing the plastic powder into a plastic sheet or a plastic film under the protection of an inert gas. The test strip provided by the present invention satisfies the test of ultra-thin plastics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastics, and more particularly to an ultra-thin test specimen of modified plastics and a preparation method and application thereof. Background Art

[0002] Plastic test strips are widely used in physical and mechanical property tests of various plastic materials. Traditional plastic test strips usually adopt a larger thickness. For example, the thickness of the national standard tensile and bending performance test strips is 4mm. The standard test strips can be prepared by injection molding and compression molding according to the national standard method. For example, after granulation, the modified plastic basically forms cylindrical particles with a diameter of 2 to 3mm and a length of 3 to 5mm. Because the melt fluidity of modified plastics, especially after filling with minerals or glass fibers, is poor. If such plastic particles are prepared according to the national standard "Preparation of injection molding specimens of plastic thermoplastic materials Part 1: General principles and preparation of multi-purpose specimens and long strip specimens" GB / T17037.1-2019 injection molding process to prepare test strips, it is difficult to prepare thinner test specimens (the size needs to reach 0.3 to 0.4mm). Even if this type of plastic particles are used to prepare test specimens according to the national standard "Compression of Plastic Thermoplastic Material Specimens" GB / T9352-2008 molding process, it is difficult to melt and hot-press the 2-3mm diameter particles into specimens with a thickness of 0.3-0.4mm. Since the welding between the particles after hot pressing is poor and the specimen strength is low, this standard is not recommended for thermoplastic reinforced materials.

[0003] However, with the continuous development of plastic materials and the expansion of their application fields, the requirements for the thickness of plastic test strips are also constantly changing. Among them, in the field of thin-walled plastic products, thinner test strips are needed to more accurately evaluate the performance of the material. For example, in the fields of thin-walled precision electronic components, flexible electronics, biomedicine, and packaging, the thickness of plastic products is usually in the range of tens to hundreds of microns, and the use of traditional thicker test strips cannot truly reflect the properties of the material. For another example, in the field of composite materials and reinforced plastics, the thickness of plastic products is usually 0.4 to 0.8 mm. The thickness of the test strips needs to be consistent with the actual parts, and the thickness of the test strips also needs to be reduced to better simulate the material structure and performance in actual applications. In these cases, the thickness of traditional test strips cannot meet the testing requirements. And it is difficult to prepare extremely thin test strips using traditional injection molding or compression molding processes.

[0004] Therefore, it is necessary to develop new process methods that can produce thinner test specimens. Summary of the invention

[0005] In order to solve the above problems, the present invention provides a modified plastic ultra-thin test specimen and a preparation method thereof. The present invention grinds plastic particles into powder without destroying the properties of the plastic and prepares the test sample under the protection of an inert gas to obtain a thinner test specimen, which can meet the testing of ultra-thin plastic samples.

[0006] Firstly, one of the purposes of the present invention is to provide an ultra-thin test strip of modified plastic.

[0007] Specifically, the thickness of the modified plastic ultra-thin test specimen is 0.3-0.9 mm, preferably 0.35-0.75 mm.

[0008] Secondly, the second object of the present invention is to provide a method for preparing the modified plastic ultra-thin test strips of the first object of the present invention.

[0009] Specifically, the preparation method comprises the following steps:

[0010] Step 1: Grind the modified plastic particles into powder;

[0011] Step 2: Under the protection of inert gas, the powder is made into a plastic sheet or a plastic film by hot pressing;

[0012] Step 3: Cut the plastic sheet or plastic film to obtain the test specimen.

[0013] More specifically, the preparation method comprises the following steps:

[0014] Step 1: Grind the modified plastic particles into powder of a certain size;

[0015] Step 2: Under the protection of inert gas, a certain amount of powder is made into a plastic sheet or a plastic film by hot pressing;

[0016] Step 3: Cut the plastic sheet or plastic film into test strips according to the sample size requirements.

[0017] Furthermore, in step one, the modified plastic is first ground into powder, and the modified plastic particles can be crushed into powder by mechanical friction and impact. During the grinding process, it is necessary to prevent the modified plastic particles from generating heat due to friction, which may lead to plastic melting and agglomeration. During the crushing process, the grinding equipment or plastic particles can be cooled by air cooling, water cooling, liquid nitrogen cooling, etc.; among them, liquid nitrogen cooling can meet the grinding and cooling requirements of all plastic particles.

[0018] Furthermore, in step 1, the particle size of the powder is controlled within the range of 300 to 700 μm, and the plastic powder of the above particle size can be screened out using 24-mesh and 50-mesh screens. The size of the powder particle size affects the test performance and hot pressing effect of the test specimen. If the particle size of the powder is less than 300 μm, it is easy to destroy the length of the filler such as glass fiber in the modified plastic, affecting the test performance of the specimen; if the particle size of the powder is greater than 700 microns, it affects the hot pressing welding, and the prepared specimen cannot meet the requirements.

[0019] Furthermore, in step 1, the modified plastic particles are selected from one or a combination of modified polyolefins, modified polyesters, modified polyamides, modified polyphenylene ethers, and modified polyphenylene sulfides. The modified plastics are modified in a manner selected from one of toughening, glass fiber reinforcement, mineral filling, and alloy modification.

[0020] Furthermore, in step 2, the inert gas is selected from one or a combination of nitrogen, argon, helium, etc. Through the protection of the inert gas, the material can be prevented from being oxidized by contact with air during the heating and melting process. The mold part of the molding machine can be sealed and filled with inert gas for protection.

[0021] Furthermore, in step 2, the hot pressing method is: after the powder is melted, pressurizing to greater than 3 MPa and maintaining the pressure for 3 to 5 minutes.

[0022] Furthermore, the test strip prepared in the present invention has a thickness of 0.3 to 0.9 mm and is a plastic sheet or a plastic film obtained by a hot pressing process, and the test strip cannot be obtained by an injection molding process.

[0023] When using a molding machine to prepare a sample strip, the thickness of the sample strip, the cavity volume of the mold and the density of the plastic can be calculated according to the required preparation, the amount of powder material can be calculated, and the corresponding measured powder can be evenly spread in the mold cavity, and then the plastic sheet or plastic film of the required thickness can be obtained through a hot pressing process.

[0024] Furthermore, according to the shape and size requirements of test specimens such as tensile and bending, the plastic sheet or plastic film can be cut into test specimens of required shape and size using scissors, shears, and cutting tools.

[0025] Again, the third object of the present invention is to provide an application of the modified plastic ultra-thin test strip which is one of the objects of the present invention.

[0026] The modified plastic ultra-thin test specimen, which is one of the purposes of the present invention, is used for testing plastics with a specimen thickness of 0.3 to 0.9 mm.

[0027] Compared with the prior art, the beneficial effects of the present invention are:

[0028] The present invention provides an ultra-thin test specimen that matches ultra-thin plastics and provides more accurate test results. The present invention also provides a simple and easy preparation method for the ultra-thin test specimen of modified plastic granular material and requires less material. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A physical picture of the test specimen prepared in Example 1 of the present invention;

[0030] Figure 2 A physical picture of the test specimen prepared in Example 2 of the present invention;

[0031] Figure 3 A physical picture of the test specimen prepared in Example 3 of the present invention;

[0032] Figure 4 This is a physical picture of the test sample prepared for the comparative example of the present invention. DETAILED DESCRIPTION

[0033] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0034] In the following examples and comparative examples, the raw materials are all derived from commercially available products.

[0035] Example 1

[0036] This example is used to illustrate the preparation of modified plastic ultra-thin test strips, and the specific steps are as follows:

[0037] The polyphenylene ether (purchased from Nantong Xingchen Synthetic Materials Co., Ltd.) particles were crushed by a pulverizer, and the powders between 300 and 700 microns were sieved through 24-mesh and 50-mesh sieves.

[0038] Select a mold with a cavity depth of 0.4 mm and a cavity area of ​​160*160 mm. According to the density of the modified plastic of 1.01 g / cm 3 The calculated powder addition amount is 10.3 g, and the actual addition amount is 12 g. Under an inert gas (nitrogen) atmosphere, the powder is evenly spread in the mold cavity, placed in a molding machine, heated and melted at 295°C for 5 minutes, pressurized to 10 MPa after melting, maintained at pressure for 5 minutes, and then cooled to obtain a plastic sheet with a thickness of 0.38 mm.

[0039] The pressed plastic sheet was prepared with scissors into dumbbell-shaped test specimens with a length of 150 mm, a width of 15 mm, and a thickness of 0.38 mm. Figure 1 shown.

[0040] Example 2

[0041] This example is used to illustrate the preparation of modified plastic ultra-thin test strips, and the specific steps are as follows:

[0042] Glass fiber reinforced polybutylene terephthalate (purchased from Ningbo Huateng Shouyan New Materials Co., Ltd.) particles were crushed by a pulverizer, and powders between 300 and 700 microns were sieved through 24-mesh and 50-mesh sieves.

[0043] Select a mold with a cavity depth of 0.4 mm and a cavity area of ​​160*160 mm. According to the density of the modified plastic of 1.5 g / cm 3 The calculated amount of powder added is 15.36 g, and the actual amount added is 18 g. Under an inert gas (nitrogen) atmosphere, the powder is evenly spread in the mold cavity, placed in a molding machine, heated and melted at 265°C for 5 minutes, pressurized to 10 MPa after melting, maintained at pressure for 4 minutes, and then cooled to obtain a plastic sheet with a thickness of 0.35 mm.

[0044] The pressed plastic sheet was prepared with scissors into dumbbell-shaped test specimens with a length of 150 mm, a width of 15 mm, and a thickness of 0.35 mm. Figure 2 shown.

[0045] Example 3

[0046] This example is used to illustrate the preparation of modified plastic ultra-thin test strips, and the specific steps are as follows:

[0047] Glass fiber reinforced nylon (purchased from Ningbo Huateng Shouyan New Materials Co., Ltd.) particles were crushed by a pulverizer, and powders between 300 and 700 microns were sieved through 24-mesh and 50-mesh sieves.

[0048] Select a mold with a cavity depth of 0.4 mm and a cavity area of ​​200*200 mm. According to the density of the modified plastic of 1.4 g / cm 3 The calculated powder addition amount is 22.4g, and the actual addition amount is 25g. In an inert gas (nitrogen) atmosphere, the powder is evenly spread in the mold cavity, placed in a molding machine, heated and melted at 260°C for 5 minutes, pressurized to 10MPa after melting, maintained at pressure for 5 minutes, and then cooled. A plastic sheet with a thickness of 0.35mm is obtained.

[0049] The pressed plastic sheet was prepared with scissors into dumbbell-shaped test specimens with a length of 150 mm, a width of 15 mm, and a thickness of 0.35 mm. Figure 3 shown.

[0050] Comparative Example

[0051] This comparative example is used to illustrate the preparation of modified plastic ultra-thin test strips, and the specific steps are as follows:

[0052] Glass fiber reinforced nylon (purchased from Ningbo Huateng Shouyan New Materials Co., Ltd.) particles were crushed by a pulverizer, and powders larger than 700 microns were sieved through a 25-mesh sieve.

[0053] Select a mold with a cavity depth of 0.4 mm and a cavity area of ​​200*200 mm. According to the density of the modified plastic of 1.4 g / cm 3 The calculated powder addition amount is 22.4g, and the actual addition amount is 25g. In an inert gas (nitrogen) atmosphere, the powder is evenly spread in the mold cavity, placed in a molding machine, heated and melted at 260°C for 5 minutes, pressurized to 10MPa after melting, maintained at pressure for 5 minutes, and then cooled. A plastic sheet with a thickness of 0.35mm is obtained.

[0054] The pressed plastic sheet was prepared with scissors into dumbbell-shaped test specimens with a length of 150 mm, a width of 15 mm, and a thickness of 0.35 mm. Figure 4 shown.

[0055] The performance tests were performed on the specimens prepared in Examples 1 to 3 and the comparative example. The tensile test was performed according to GB / T 1040.3-2018 standard at a tensile rate of 5 mm / min. The test results are shown in Table 1.

[0056] Table 1:

[0057] Tensile Strength Spline shape Example 1 73.3MPa Uniform and complete surface Example 2 50.3MPa Uniform and complete surface Example 3 71.4MPa Uniform and complete surface Comparative Example 1 18.2MPa There are obvious holes on the surface, and the plastic particles are not completely welded.

[0058] As can be seen from Table 1, the splines obtained in Examples 1 to 3 have uniform morphology and excellent tensile strength, and can be used for testing plastic samples; while the splines obtained in the comparative example have obvious voids on the surface, incomplete welding, and low tensile strength, and cannot meet the requirements for testing plastic samples.

[0059] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified plastic ultra-thin test strip, wherein the thickness of the test strip is 0.3 to 0.9 mm.

2. The modified plastic ultra-thin test specimen according to claim 1, characterized in that: The thickness of the test specimen is 0.35-0.75 mm.

3. The method for preparing the modified plastic ultra-thin test strip according to any one of claims 1 to 2, the method comprising the following steps: Step 1: Grind the modified plastic particles into powder; Step 2: Under the protection of inert gas, the powder is made into a plastic sheet or a plastic film by hot pressing; Step 3: cutting the plastic sheet or plastic film to obtain the test specimen.

4. The method for preparing the modified plastic ultra-thin test strip according to claim 3, characterized in that: In the step 1, the grinding method of the modified plastic particles is selected from one or a combination of mechanical friction and impact.

5. The method for preparing the modified plastic ultra-thin test strip according to claim 3, characterized in that: In the step 1, the particle size of the powder is in the range of 300 to 700 μm.

6. The method for preparing the modified plastic ultra-thin test strip according to claim 3, characterized in that: In the step 1, the modified plastic particles are selected from one or a combination of modified polyolefins, modified polyesters, modified polyamides, modified polyphenylene ethers, and modified polyphenylene sulfides.

7. The method for preparing the modified plastic ultra-thin test strip according to claim 6, characterized in that: The modification method of the modified plastic is selected from toughening, glass fiber reinforcement, mineral filling and alloy modification.

8. The method for preparing the modified plastic ultra-thin test strip according to claim 3, characterized in that: In the step 2, the inert gas is selected from one or a combination of nitrogen, argon and helium.

9. The method for preparing the modified plastic ultra-thin test strip according to claim 3, characterized in that: In the step 2, the hot pressing method is: after the powder is melted, pressurizing to greater than 3 MPa, and maintaining the pressure for 3 to 5 minutes.

10. Use of the modified plastic ultra-thin test specimen according to any one of claims 1 to 2 for testing plastics with a thickness of 0.3 to 0.9 mm.